The Effect of Intellectual Capital and Corporate Governance on Firm Value with Profitability as a Moderating Variable - Claudia Febby Maharanie (International Journal Labs, 2025)
This study aims to examine, analyze, and develop the effect of intellectual capital and corporate governance on firm value, with profitability as a moderating variable. The sample was selected using a purposive sampling technique from a population of the 35 coal mining companies listed on the Indonesia Stock Exchange (IDX). This resulted in a sample of 24 companies over a 4 year research period, totaling 96 data observations used in this study. This research employs a quantitative descriptive method. Hypothesis testing in this research utilizes Moderated Regression Analysis (MRA) and classical assumption tests using Eviews 12 application. The results indicate that intellectual capital and corporate governance does not significant effect on firm value. However, profitability as a moderation variable does not strengthen the influence of intellectual capital and corporate governance on firm value.